The Effect of Altitude on the Quality of Honey Pineapple (Ananas comosus (L.) Merr) - Zakia Adillah, Arwa Ghina; Hidayanti, Dina Ulfa; Rodhiyah, Afsika; Wahyuni, Siti (Jurnal Agrosci, 2024)
Pineapple (Ananas comosus (L.) Merr) is a Bromeliaceae plant. Pineapple plants are widely cultivated in several countries, and Indonesia is one of the largest producers of pineapples. This study aims to determine the optimal height of the growing place for the quality of honey pineapple. The research was carried out at the Laboratory of the Faculty of Agriculture, Gunung Jati Swadaya University, in July-August 2024. The research used the purposive sampling method, data processing was done using a complete random design, and further BNT tests were performed. The experimental factors carried out were the altitude of the observation location, namely 1019 m above sea level (high), 643 m above sea level (medium), and 384 m above sea level (low). The study results showed that the height of the place had a natural effect on the quality of honey pineapple. The heaviest fruit weight (566.64 grams) was obtained on plants at 643 m above sea level (medium altitude). The highest dissolved density is produced in plants at an altitude of 643 m above sea level. The highest vitamin C and water content levels are produced in plants at 1019 m above sea level. The highest anthocyanin levels (0.01700) were obtained in plants at an altitude of 643 m above sea level, and the most extended shelf life was produced in plants at 384 m above sea level (lowlands)